Cover Image. Issue 5 (1st May 2021) - Unknown
Abstract : A triptych of maximum projections of two photon images of 21dpf Tg(batf3MIN:GFP) transgenic fish cleared and immunostained for batf3MIN:GFP+ vascular and lymphatic vessels (green) and acetylated tubulin axons (magenta); From: New reporter zebrafish line unveils heterogeneity among lymphatic endothelial cells during development ; Maxence Frétaud, Nam Do Khoa, Armel Houel, Aurélie Lunazzi, Pierre Boudinot and Christelle Langevin; DevDyn 250:5, pp. 701–716.